INVESTIGATION FOR THE DEVELOPMENT AND APPLICATION OF EFFICIENT COOLING-LUBRICATING FLUIDS (Journal of Science-Innovative Research in Uzbekistan, 2025)
This study explores the formulation and application of efficient cooling-lubricating fluids (CLFs) for metal cutting processes. Four types of fluids—mineral oil-based, vegetable oil-based, synthetic esters, and water-based emulsions—were analysed in terms of their viscosity, thermal conductivity, flash point, and environmental compatibility. Experimental turning operations evaluated their effect on tool wear, surface roughness, and cutting temperature. The findings demonstrate that vegetable oil-based CLFs exhibit superior performance, highlighting their potential as eco-friendly and effective alternatives in machining operations.